Factors Contributing to the Successful Tuberculosis Preventive Treatment in Latent Tuberculosis: Literature Review - Saputra, Randi Jaya; Sulistyawati, Sulistyawati; Sukesi, Tri Wahyuni (Sarana Ilmu Indonesia (salnesia), 2025)
In Indonesia, the coverage of tuberculosis preventive treatment in household contacts has not reached the national target (58%) of 2,6%. In the age group <5 years and other risk groups, the coverage was 5,1% and 3,1% , and the coverage in PLHIV was 6% with a national target of 50%. This literature review aimed to explore the factors that determine successful completion of TB preventive treatment. The literature review approach was conducted using databases from PubMed, Google Scholar, and ProQuest. Articles selected were full text, open access, between 2015 and 2025, and not a literature review, systematic review, or meta-analysis. From 487,952 articles based on keywords, 16 articles were selected that met the objectives and inclusion criteria of this study. The 16 articles were then entered into a matrix table to identify research results that were factors associated with the completion rate of tuberculosis preventive treatment (TPT) in patients with pulmonary tuberculosis. High TPT completion was supported by demographic factors, safe treatment regimens with minimal side effects, technology-based community approaches, improved access and adherence, tuberculosis education, social support, integrated health care systems and health policies.